Structure Characterization, Immunological Activity, and Mechanism of a Polysaccharide From the Rhizome of Menispermum dauricum DC - Yang, Pei; Jin, Juan; Ma, Yan; Wang, Fengshan; Li, Yaying; Duan, Baoguo; Zhang, Yongqing; Liu, Yuhong (Frontiers in Nutrition, 2022)
The purpose of this study was to investigate the structural characterization and immunological activity in vitro and in vivo of a polysaccharide from the rhizome of Menispermum dauricum. A new polysaccharide named MDP was isolated from the rhizome of Menispermum dauricum by hot water extraction, ethanol precipitation, anion-exchange and gel-filtration chromatography. MDP was homogeneous and had a molecular weight of 6.16×103 Da, and it was an α-D-glucan containing a (1→6)-linked backbone, with a glucosyl residue at the C-3 position along the main chain. MDP exhibited immunological activity in vitro, which could significantly promote the proliferation and phagocytosis of RAW264.7 cells and the release of TNF-α and IL-6 factors. For immunological activity in vivo. MDP could significantly increase the thymus and spleen indices, enhance the macrophage function, increase the level of cytokine (IL-6 and TNF-α) and immunoglobulin IgM in the serum and regulate T lymphocyte subsets. Furthermore, MDP elevated the expression of the critical nodes in the TLR4-MyD88 signaling pathways in vivo. These results support the concept that MDP may exhibit immunological activity through TLR4-MyD88 signaling pathway in vivo.